Action mechanisms of petroleum hydrocarbons present in waters impacted by an oil spill on the genetic material of Allium cepa root cells - Leme, Daniela Morais [UNESP]; de Angelis, Dejanira de Franceschi [UNESP]; Marin-Morales, Maria Aparecida [UNESP] (Elsevier B.V., 2008)
Chromosomal aberration (CA) assays have been widely used, not only to assess the genotoxic effects of chemical agents, but also to evaluate their action mechanisms on the genetic material of exposed organisms. This is of particular interest, since such analyses provide a better knowledge related to the action of these agents on DNA. Among test organisms, Allium cepa is an outstanding species due to its sensitivity and suitable chromosomal features, which are essential for studies on chromosomal damage or disturbances in cell cycle. The goal of the present study was to analyze the action mechanisms of chemical agents present in petroleum polluted waters. Therefore, CA assay was carried out in A. cepa meristematic cells exposed to the Guaeca river waters, located in the city of Sao Sebastiao, SP, Brazil, which had its waters impacted by an oil pipeline leak. Analyses of the aberration types showed clastogenic and aneugenic effects for the roots exposed to the polluted waters from Guaeca river, besides the induction of cell death. Probably all the observed effects were induced by the petroleum hydrocarbons derived from the oil leakage. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Allium cepa; chromosomal aberrations; aneugenic and clastogenic agents; cell death; polluted waters; petroleum hydrocarbons